A case of ALS with posterior cortical atrophy. Issue 7 (2nd October 2019) - Nijboer, Tanja C. W.; Nitert, Bram; Westeneng, Henk-Jan; Van Den Berg, Leonard H.; van Es, Michael A.
Abstract: Here, we provide a case-report of an amyotrophic lateral sclerosis (ALS) patient with cognitive deficits best defined as posterior cortical atrophy (PCA). This is an unusual finding as ALS forms a spectrum with frontotemporal dementia (FTD), whereas PCA is predominantly associated with Alzheimer's disease pathology. We hypothesize on whether ALS with PCA might be an under recognized phenotype considering multiple imaging studies in ALS have also reported (asymptomatic) parietal atrophy.